Eliminating the gap between the use of assistive technologies and the inclusion of people with intellectual disabilities in leisure activities. (April 2021) - Dratsiou, Ioanna; Metaxa, Maria; Romanopoulou, Evangelia; Dolianiti, Foteini; Spachos, Dimitris; Bamidis, Panagiotis D
Information and Communication Technology (ICT) tools and Assistive Technologies (AT) can support people with Down Syndrome (PDS) and Intellectual Disabilities (PID) in increasing their self-confidence and independence, enhancing skills, and competences, participating in leisure activities. For families of PDS/PID, professionals, non-formal caregivers and volunteers, the challenge is to appreciate the benefits of ICT Tools in promoting inclusion. The aim of this study is to present the interdisciplinary and multidimensional scope of the DS Leisure project aiming at promoting the inclusion of PDS/PID through innovative ICT tools and their participation in inclusive leisure activities. Particularly, 24 individuals were asked to assess the global satisfaction and performance of PDS/PID, as well as the exploitation of ICT tools. Findings suggested that PDS/PID specific social, decision-making, and communication skills were significantly improved after their participation in the Experiential Activity and the e-Training platform was positively rated and considered a constructive learning experience.